Analisis Kebijakan Peraturan Daerah Tentang Kenaikan Tarif Parkir Di Dki Jakarta - Satya Pranata Asmara (UIR Press, 2020)
DKI Jakarta as a central business unit (CBD) is a city center located in the middle of the city which is the center of social, economic, cultural and political life and is a zone with a high degree of accessibility and mobility in a city. The fundamental effort that must be made by the DKI Government in overcoming the congestion problem is to shift the mindset of the public using private vehicles to public transportation. One of the policies whose implementation has received criticism and opposition from the public is the policy of increasing parking rates. This policy, which is implemented through an increase in parking rates, is planned to be charged Rp. 50 thousand per hour, potentially causing opposition from the public. The policy of increasing parking rates in the DKI Jakarta area as a solution to solving congestion problems in DKI Jakarta was born from the results of the analysis of three approaches, namely empirical, evaluative, and normative. The Regional Regulation regarding Parking Rate Increase in the DKI area is actually a policy set in order to encourage private vehicle drivers to switch (shifting) to public / mass transportation, because with expensive parking rates it is expected that private vehicle drivers will be reluctant to drive privately. The expected result is the volume of private car use which is the main cause of congestion in DKI Jakarta. The policy of the DKI Jakarta Government through the stipulation of Regional Regulations on Increasing Parking Rates in the DKI Jakarta area was born through a three-approach process, namely: empirical, evaluative, and normative approaches so that the policy analysis cycle before policy determination has been carried out comprehensively. Approach processes: empirical, evaluative, and normative that have been carried out in the analysis before the birth of this policy should be synergized again by conducting an analysis after the enactment of this policy with an independent body outside the government bureaucracy, so as to obtain a win win solution in overcoming problems that may arise later. days and can accommodate the interests of local government and society